Comment on "Fixed-Time Attitude Control for Rigid Spacecraft With Actuator Saturation and Faults" - Esmailzadeh, Seyed Majid; Golestani, Mehdi (IEEE transactions on control systems technology, 2019)
Based on a new fixed-time sliding mode control, a finite-time control for attitude stabilization of a rigid spacecraft subject to external disturbance, actuator faults, and input saturation has been presented by Jiang et al. The main objective of this comment is to point out a mistake in a critical theorem by Jiang et al., which resulted in the ineffectiveness of the proposed controller.